Wide-Angle Beam-Scanning Reflectarray With Mechanical Steering - Wu, Geng-Bo; Qu, Shi-Wei; Yang, Shiwen (IEEE transactions on antennas and propagation, 2018)
A novel wide-angle beam-scanning phase synthesis method, namely, multibeam phase matching method is introduced in this paper. It takes full advantage of angle sensitivity characteristic of reflectarray elements to improve the beam-scanning performance of reflectarrays. In the process of reflectarray aperture synthesis, the beam deviation factors and reference phases are optimized to minimize the total phase error, and the geometries of each element are optimized to match the desired phase shifts at multiple beam-scanning angles after taking into account the real incident angles. Then, a 16 × 16 -element reflectarray antenna with square patch elements operating at 12 GHz has been designed, simulated, and fabricated. The measured results show that a gain variation less than 1.7 dB across the scan coverage from −45° to +45° can be achieved by mechanically rotating the feed antenna, which shows a considerable improvement in beam-scanning performance as compared to the reflectarrays designed using conventional single-focus and bifocal methods.